Penerapan Konsep Taman Rakyat Pada Interior Pusat Seni Kriya Nusantara di Surabaya - Tjoanda, Stella (Intra, 2014)
Design of Art & Craft Center in Surabaya Indonesia is means to introduce one of Indonesian art, which is Seni Kriya that is derived from all regions in Indonesia. This project is expected to attract the public to know what Seni KriyaÂ are, thus it will not be forgotten and be able to evolve as part of the creative industry in the international market. This design concept is